How Does Employee–Organization Relationship Affect Work Engagement and Work Well-Being of Knowledge-Based Employees? - Che, Yi; Zhu, Jian; Huang, Huawei (Frontiers in Psychology, 2022)
In the employment relationship, organizational factors are the main factors that affect employee behavior. Especially for knowledge workers, it is even more crucial for organizations to give enough attention to their individual needs. Based on Existence, Relatedness, and Growth (ERG) theory, this study constructs a moderated mediating model to explore how employee-organization relationship (EOR) impact on work engagement and work well-being of knowledge employees. In this study, existence-relatedness-growth need satisfaction is used as a mediator and perceived symbiotic relationship is used as a moderator. Data collected from 791 knowledge employees in higher education institutions from more than 20 provinces and cities in China is used to test the model. The results show that (1 )EOR has significant positive effects on work engagement and work well-being. (2) need satisfaction for relatedness partially mediates the effects of EOR on work engagement and work well-being. (3) need satisfaction for growth mediates EOR’s effect on work engagement, while the mediating role of need satisfaction for growth between EOR and work well-being is unsupported. (5) the mediating role of need satisfaction for existence of EOR on both work engagement and work well-being are unsupported. (6) perceived symbiotic relationship moderates the relationship between EOR and work engagement and work well-being. The findings have theoretical significance in expanding the research field of EOR and providing a basis for organizations to implement EOR strategies.